Impaired vascular redox signalling in the vascular complications of obesity and diabetes mellitus - Akoumianakis, I; Antoniades, C (Mary Ann Liebert, 2017)
Significance: Oxidative stress, a crucial regulator of vascular disease pathogenesis, may be involved in the vascular complications of obesity, systemic insulin resistance and diabetes mellitus. Recent advances: Excessive production of reactive oxygen species in the vascular wall has been linked with vascular disease pathogenesis. Recent evidence has revealed that vascular redox state is dysregulated in cases of obesity, systemic insulin resistance and diabetes mellitus, potentially participating to the well-known vascular complications of these disease entities. Critical issues: The detrimental effects of obesity and the metabolic syndrome on vascular biology have been extensively described at a clinical level. Furthermore, vascular oxidative stress has often been associated with the presence of obesity and insulin resistance as well as a variety of detrimental vascular phenotypes. However, the mechanisms of vascular redox state regulation under conditions of obesity and systemic insulin resistance, as well as their clinical relevance, are not adequately explored. In addition, the notion of vascular insulin resistance, and its relationship with systemic parameters of obesity and systemic insulin resistance, is not fully understood. In this review, we present all the important components of vascular redox state and the evidence linking oxidative stress with obesity and insulin resistance. Future directions: Future studies are required to describe the cellular effects and the translational potential of vascular redox state in the context of vascular disease. In addition, further elucidation of the direct vascular effects of obesity and insulin resistance is required for better management of the vascular complications of diabetes mellitus.